2015
DOI: 10.1002/ejic.201500267
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Bimodal Mesoporous Fe3O4@SiO2 Composite for Efficient Removal of Methylene Blue

Abstract: A facile self-assembly synthetic procedure was exploited to fabricate mesoporous-silica-capped Fe 3 O 4 mesoporous clusters, so-called bimodal mesoporous Fe 3 O 4 @SiO 2 composites. Structural characterization demonstrated that the core of the Fe 3 O 4 clusters is coated with a mesoporous silica shell of uniform size distribution. Moreover, unprecedentedly good tunability of the core size (180-1700 nm) and the shell thickness (20-75 nm) is achievable by changing the synthetic parameters. Application of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 31 publications
(11 reference statements)
0
12
0
1
Order By: Relevance
“…HA coated MNPs remove MB from aqueous solution [234]. Mesoporous-silica-capped Fe3O4 mesoporous clusters exhibit excellent adsorption of MB from aqueous solution and is easily regenerated by the photo-Fenton degradation reaction as a result of its high specific surface area, accessible pore channels, and good magnetic separation properties [235]. Fe3O4/GO nanocomposites effectively remove Congo red as an anionic dye and MB as a cationic dye in aqueous solutions [236].…”
Section: Adsorptive and Separative Removal Of Organic Contaminantsmentioning
confidence: 99%
“…HA coated MNPs remove MB from aqueous solution [234]. Mesoporous-silica-capped Fe3O4 mesoporous clusters exhibit excellent adsorption of MB from aqueous solution and is easily regenerated by the photo-Fenton degradation reaction as a result of its high specific surface area, accessible pore channels, and good magnetic separation properties [235]. Fe3O4/GO nanocomposites effectively remove Congo red as an anionic dye and MB as a cationic dye in aqueous solutions [236].…”
Section: Adsorptive and Separative Removal Of Organic Contaminantsmentioning
confidence: 99%
“…[6][7][8] Over the years, mesoporous SiO 2 has attracted attention as support material for a variety of metals and metal oxides, and has been utilized in applications such as catalysis, sensors, drug delivery, adsorption, and removal of heavy metal ions. [9][10][11][12] Mesoporous SiO 2 , owing to its high specific surface area, large pore volume, high thermal stability, and long, ordered pore channels, can stimulate chemical reactivity and physical adsorption of water molecules and so has attracted significant interest in designing efficient RH sensors. [13][14][15] Yuan et al modified the SiO 2 framework by using ZnO nanoparticles through a simple, one-step sol-gel route.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation results can be obtained using the Beer–Lambert law. It has been reported that the iron content influences both the textural characteristics of the photocatalyst and the Fenton reaction . It can be observed that with an increase in the dosage of FeCl 3 from 1 mL to 3 mL, which means an increase in Fe 2 O 3 nanoparticles on the surface of g‐C 3 N 4 , the catalytic activity is enhanced gradually, indicating that a suitable amount of dispersion of Fe 2 O 3 nanoparticles is beneficial for the enhancement of the catalytic activity.…”
Section: Resultsmentioning
confidence: 98%
“…The second refers to the continuous loss of iron ions and the formation of solid sludge. Several economic and environmental drawbacks have been reported to occur with the Fenton sludge …”
Section: Introductionmentioning
confidence: 99%